Efeito da diversidade de habitats sobre o desenvolvimento populacional do camarão-da-amazônia - Santos, Michélle Roberta dos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The objective of this study was to test the hypothesis in which the development of the population structure of amazonian prawn, Macrobrachium amazonicum, is affected by the heterogeneity of habitats from the bottoms of bodies of water. Twelve mesocosms of natural background were used, where each mesocosm had an area of ~0.01 ha and a depth of ~1 m, and with an approximate volume of 100 m3. The mesocosms were stocked with 22/m2 juveniles of amazonian prawn and 1.1/m2 of juvenile tilapia (which composed the nektonic extract) in three different treatments: mesocosm with substrate made of geotextile blanket (MG), mesocosm with substrate made from bamboo (BB), and then mesocosm without substrate (SS). The prawn were collected monthly and at the end of the experiment in order to assess population structure, ovarian stage, body mass and length, sex-ratio, and survival. The presence of the substrates in the mesocosms increased the frequency of the CC morphotypes, accelerated the appearance of the GC1 and GC2 morphotypes, decreased the frequency of the TC morphotype at the end of the experiment, increased the size of males and females, and increased the frequency of ovarian stages IV and V. The effect was more pronounced with the presence of the MG substrate. On the other hand, the survival rate was significantly higher in the mesocosms without substrates even though the values were quite similar. The sex-ratio did not differ significantly between treatments with or without the addition of substrate. Therefore, the presence and the type of substrate added to the bottoms of water systems present an effect on the population growth of M. amazonicum, confirming the initial hypothesis which stated that population structure is dependent on the heterogeneity of habitats

O objetivo deste trabalho foi testar a hipótese de que o desenvolvimento da estrutura populacional do camarão-da-amazônia, Macrobrachium amazonicum, é afetada pela heterogeneidade de habitats do fundo dos corpos de água. Foram utilizados doze mesocosmos de fundo natural, com área de ~0,01 ha e profundidade ~1 m, com volume aproximado 100 m3. Os mesocosmos foram povoados com 22 juvenis de camarões/m2 e 1,1 alevino de tilápias (que compuseram o extrato nectônico) em três tratamentos: mesocosmo com substrato feito de manta Geotêxtil (MG), mesocosmo com substrato feito de bambu (BB), mesocosmo sem substrato (SS). Mensalmente e ao final do experimento, os camarões foram coletados, para avaliar a estrutura populacional, estágio ovariano, massa e comprimento corporal, sex-ratio e sobrevivência. A presença dos substratos nos mesocosmos aumentou a frequência dos morfotipos CC, acelerou o aparecimento dos morfotipos GC1 e GC2, diminuiu a frequência do morfotipo TC ao final do experimento, aumentou o tamanho de machos e fêmeas e a frequência dos estágios ovarianos IV e V. O efeito foi mais acentuado com a inclusão do substrato MG. Por outro lado, a sobrevivência foi significativamente maior nos mesocosmos sem substratos, embora os valores tenham ficado muito próximos. O sex-ratio não diferiu significativamente entre os tratamentos com adição ou não de substrato. Portanto, a presença e o tipo de substrato adicional ao fundo presente nos corpos de água afetam o desenvolvimento populacional de M. amazonicum, confirmando a hipótese inicial que esta é dependente da heterogeneidade de habitats
Keywords: Camarão; Macrobrachium; Substratos; Habitat (Ecologia); Ecologia; Heterogeneidade ecológica; Ecology